PENENTUAN KADAR LIPOPROTEIN RAPATAN TINGGI (HIGH DENSITY) DENGAN DUA PEREAKSI (REAGEN) BERBEDA MENGGUNAKAN HITACHI 902 - I. Hutagalung; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Reagent selection is one of the factors that could influence the quality of laboratory results. The use of open system tools gives thepossibility to choose the best reagents, including the reagent for high density lipoprotein (HDL) determination. The aim of this studywas to compare HDL level determination using two different reagents measured by Hitachi 902. A cross sectional study was done fromJanuary to February 2007 in Ratulangi Medical Centre Laboratory, Makassar. From 47 samples we found that the mean HDL levelusing Daichi reagent was 50.47 mg/dl ranging from 45.99 mg/dl to 54.94 mg/dl and the mean using Roche reagent was 56.23 mg/dlranging from 50.93 mg/dl to 61.53 mg/dl with p = 0.098, and Pearson Correlation was 0.900 with p = 0.000. There was no significantdifference between HDL level measured by Hitachi 902 using Daichi and Roche reagents.